2002
DOI: 10.1007/s00280-002-0469-8
|View full text |Cite
|
Sign up to set email alerts
|

STEALTH liposome-encapsulated cisplatin (SPI-77) versus carboplatin as adjuvant therapy for spontaneously arising osteosarcoma (OSA) in the dog: a randomized multicenter clinical trial

Abstract: While STEALTH liposome encapsulation of cisplatin allowed the safe administration of five times the maximally tolerated dose of free cisplatin to dogs without concurrent hydration protocols, this did not translate into significantly prolonged DFS or OS. However, a larger proportion of dogs receiving SPI-77 enjoyed long-term DFS when compared with dogs receiving carboplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 11 publications
3
49
1
Order By: Relevance
“…Data from 20 studies were included in this IPDMA, of which 11 studies were previously published (Kurzman et al, 1995;Berg et al, 1997;Kirpensteijn et al, 2002;Vail et al, 2002;Morello et al, 2003;Moore et al, 2007;Bacon et al, 2008;Kow et al, 2008;Phillips et al, 2009;Sottnik et al, 2010). 19 studies reported solely on large breed dogs, while the unpublished study of Dr. Amsellem included 36 small breed canines.…”
Section: Resultsmentioning
confidence: 99%
“…Data from 20 studies were included in this IPDMA, of which 11 studies were previously published (Kurzman et al, 1995;Berg et al, 1997;Kirpensteijn et al, 2002;Vail et al, 2002;Morello et al, 2003;Moore et al, 2007;Bacon et al, 2008;Kow et al, 2008;Phillips et al, 2009;Sottnik et al, 2010). 19 studies reported solely on large breed dogs, while the unpublished study of Dr. Amsellem included 36 small breed canines.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Encapsulation of cisplatin in liposomes shows a better antitumoral efficacy compared to free drug in dogs with osteosarcoma. 10 Liposomal topotecan exhibits a better pharmacokinetic profile and an improved antitumor efficacy than the free drug in murine and human experimental tumors. 11 Moreover, encapsulation of vincristine (VCR) in liposomes increased the antitumor efficacy in mice bearing L-1210 and P-388 murine leukemias, compared to the free drug.…”
mentioning
confidence: 99%
“…[4][5][6][7][8] Another important prognostic factor identified for dogs with appendicular osteosarcoma is histologic grade. High grade tumors with histologic evidence of tumor growth into vessels or lymphatics, a high number of mitoses, increased cellular pleomorphism, small amounts of tumor matrix, and more than 50% necrosis in the tumor biopsy specimen had a worse prognosis compared with low grade tumors.…”
mentioning
confidence: 99%